Modified aramid nanofiber and preparation method thereof
By employing a process involving mechanical grinding, chemical pretreatment, low-pressure homogenization intercalation, ultrasonic chemical bonding, and high-pressure homogenization, the problems of uneven distribution and easy detachment of carbon nanotubes in aramid nanofibers have been solved, enabling the multifunctionality of aramid nanofibers suitable for applications such as flexible electronics, electromagnetic shielding, and sensing.
Patent Information
- Application Number
- CN202611050486.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-08-25
AI Technical Summary
Existing technologies struggle to achieve uniform distribution and secure anchoring of carbon nanotubes within aramid nanofibers, leading to their easy detachment during processing. This fails to meet the demands of high-end composite materials and flexible sensing for multifunctional integrated nanomaterials.
The process flow of mechanical grinding, KOH/DMAC chemical pretreatment, low-pressure homogenization intercalation, ultrasonic chemical bonding and high-pressure homogenization is adopted. Through the synergistic effect of each stage, the dispersion uniformity and interfacial bonding strength of carbon nanotubes in aramid nanofibers are improved.
The uniform distribution and firm anchoring of carbon nanotubes in aramid nanofibers were achieved, endowing aramid nanofibers with multifunctional properties such as electrical and thermal conductivity, making them suitable for large-scale production.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention specifically relates to a modified aramid nanofiber and its preparation method, belonging to the field of polymer nanocomposite materials technology. Background Technology
[0002] Aramid fibers possess high strength, high modulus, excellent thermal stability, and resistance to chemical corrosion, making them promising for applications in aerospace, military equipment, electronics, and advanced composite materials. In recent years, the nanostructuring of macroscopic aramid fibers to obtain aramid nanofibers has been developed, endowing materials with one-dimensional nanoscale characteristics, ultra-high aspect ratio, high specific surface area, and abundant surface functional groups, demonstrating broad application prospects in nanocomposite materials, flexible electronic devices, high-efficiency filtration membranes, and energy storage materials. However, conventional aramid fiber nanostructuring methods, such as deprotonation, chemical polymerization, and physical-mechanical methods, produce aramid nanofibers with limited functionality, lacking electrical conductivity, thermal conductivity, and electromagnetic shielding properties. These limitations make it difficult to directly meet the demands of high-end composite materials, smart wearables, and flexible sensing for multifunctional integrated nanomaterials.
[0003] To endow aramid nanofibers with more functionality, introducing functional nanofillers into the system is the most direct and effective strategy. Carbon nanotubes, due to their excellent mechanical, electrical, and thermal properties, have become ideal polymer-reinforcing fillers. However, existing technologies for preparing carbon nanotube-modified aramid fibers or aramid nanofibers generally face technical challenges such as poor nanotube dispersion, weak interfacial bonding with the aramid matrix, and easy detachment during processing.
[0004] To address these issues, researchers have proposed various methods for modifying aramid fibers with carbon nanotubes. For example, patent application CN101831800A discloses a method for modifying aramid fibers with carbon nanotubes. This method first introduces free amino groups onto the surface of the aramid fiber through isocyanate treatment, and then reacts these amino groups with carboxylated carbon nanotubes under ultrasonic assistance. This allows some carbon nanotubes to penetrate the fiber interior, while others are fixed to the surface via amide bonds. Although this method achieves chemical bonding, the depth and uniformity of carbon nanotube penetration into the fiber interior are limited by the dense core-sheath structure of aramid fibers, making it difficult to achieve a sufficient and uniform distribution of carbon nanotubes within the fiber. Furthermore, the limited number of amide bond sites and lack of mechanical anchoring effect make the carbon nanotubes prone to detachment during subsequent processing. Finally, the treated product remains macroscopic aramid fiber, failing to yield nanoscale modified fibers.
[0005] Therefore, how to achieve uniform distribution and firm anchoring of carbon nanotubes in nanoscale aramid fibers has become a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0006] This invention addresses the shortcomings of existing technologies by providing a modified aramid nanofiber and its preparation method. The invention utilizes a complete process flow involving mechanical pulping and KOH / DMAC chemical pretreatment of aramid fibers. This process involves low-pressure homogenization intercalation, ultrasonic chemical bonding, and high-pressure homogenization of carboxylated carbon nanotubes into the pretreated aramid fibers. Through synergistic effects at each stage, the dispersion uniformity, interfacial bonding strength, and anti-detachment properties of carbon nanotubes in the aramid nanofibers are significantly improved, and the aramid nanofibers are endowed with multifunctional properties such as electrical and thermal conductivity. This method is continuous, simple to operate, and suitable for large-scale production.
[0007] The technical solution of this invention to solve the above-mentioned technical problems is as follows: a method for preparing modified aramid nanofibers, the preparation method comprising the following steps: S1. The aramid fiber is first mechanically pulped and then chemically pretreated to obtain pretreated aramid fiber pulp. S2. Carbon nanotubes are ultrasonically dispersed evenly in a mixed acid solution and then subjected to a carboxylation reaction to obtain carboxylated carbon nanotubes. S3. Mix the obtained carboxylated carbon nanotubes with the pretreated aramid fiber slurry evenly to obtain a mixed slurry; S4. The mixed slurry is subjected to low-pressure homogenization to obtain aramid fiber slurry with carboxylated carbon nanotubes intercalated. S5. The aramid fiber slurry with carboxylated carbon nanotubes intercalated is subjected to ultrasonic reaction to obtain carbon nanotube modified aramid fiber slurry. S6. The carbon nanotube-modified aramid fiber slurry is subjected to high-pressure homogenization to obtain carbon nanotube-modified aramid nanofibers. Steps S1 and S2 are not in any particular order.
[0008] Further, in step S1, the mechanical treatment is a pulping process, with a pulping gap of 0.1mm to 0.5mm and a pulping speed of 20,000 rpm to 50,000 rpm.
[0009] Further, in step S1, a chemical pretreatment is performed in a mixed solution of N,N-dimethylacetamide (DMAC) and potassium hydroxide (KOH); In the mixed solution, the mass concentration of potassium hydroxide is 0.5%~2%; the mass ratio of aramid fiber to the mixed solution is 1:(100~200).
[0010] Further, in step S1, the length of the aramid fiber after pulping is 50μm~100μm and the diameter is 10μm~30μm; The chemically pretreated aramid fibers have a length of 20μm~60μm and a diameter of 5μm~20μm.
[0011] Furthermore, in step S1, the reaction temperature of the chemical pretreatment is 60~80℃, and the reaction time is 2~4h; In step S2, the carboxylation reaction is carried out at a temperature of 60-80°C for 4-10 hours.
[0012] Further, in step S2, the mixed acid is sulfuric acid and nitric acid; the volume ratio of sulfuric acid to nitric acid is (1~3):1.
[0013] Furthermore, in step S4, the low-pressure homogenization pressure is 20MPa~40MPa, and the homogenization time is 1~2h; In step S6, the high-pressure homogenization pressure is 100MPa~120MPa, and the homogenization time is 0.5~1.5h.
[0014] Furthermore, the high-pressure homogenization pressure is 3 to 5 times that of the low-pressure homogenization pressure.
[0015] Furthermore, in step S5, the frequency of the ultrasonic reaction is 20kHz~30kHz, the reaction time is 1~2h, and the reaction temperature is 60℃~80℃.
[0016] The present invention also provides a modified aramid nanofiber, which is prepared by the preparation method provided by the present invention.
[0017] The beneficial effects of this invention are: (1) This invention uses a step-by-step synergistic process of “low-pressure homogeneous intercalation, ultrasonic chemical bonding, and high-pressure homogeneous peeling” to enable carboxylated carbon nanotubes to enter the interlayer and amorphous region of the fiber when the aramid fiber is in a swollen state through low-pressure homogeneous shearing and stretching. Subsequently, during the ultrasonic reaction, the carboxyl groups on the surface of the carbon nanotubes chemically bond with the amide groups on the aramid molecular chain (forming amide bonds, ionic bonds or multiple hydrogen bonds). Finally, while the aramid fiber is split into nanofibers by high-pressure homogenization, the carbon nanotubes are firmly attached to the surface of the nanofibers or embedded in their interior through chemical bonds.
[0018] (2) In this invention, carbon nanotubes are first modified by carboxylation to improve their dispersibility in polar solvents. Then, they are uniformly intercalated into the interior of swollen aramid fibers by low-pressure homogenization pre-dispersion. Finally, the peeling of aramid nanofibers during high-pressure homogenization further "segments" the carbon nanotubes and fixes them on the surface of the nanofibers, thereby achieving a uniform distribution of carbon nanotubes at the nanoscale.
[0019] (3) Pure aramid nanofibers are insulators and have limited functionality, making it difficult to meet the application requirements of flexible electronics, electromagnetic shielding, and sensing. By introducing carbon nanotubes, this invention successfully endows aramid nanofibers with excellent electrical conductivity, thermal conductivity, and electromagnetic shielding properties, making the products of this invention have broad application prospects in flexible wearable devices, aerospace structural and functional integrated materials, and high-performance lithium battery separators. Detailed Implementation
[0020] The specific embodiments of the present invention will be described in detail below. The present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar modifications without departing from the spirit of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed.
[0021] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used is for describing particular embodiments only and is not intended to limit the invention.
[0022] This invention provides a method for preparing modified aramid nanofibers, the method comprising the following steps: S1. The aramid fiber is first mechanically pulped and then chemically pretreated to obtain pretreated aramid fiber pulp. S2. Carbon nanotubes are ultrasonically dispersed evenly in a mixed acid solution at room temperature and then subjected to a carboxylation reaction to obtain carboxylated carbon nanotubes. S3. Mix the obtained carboxylated carbon nanotubes with the pretreated aramid fiber slurry evenly to obtain a mixed slurry; S4. The mixed slurry is subjected to low-pressure homogenization to obtain aramid fiber slurry with carboxylated carbon nanotubes intercalated. S5. The aramid fiber slurry with carboxylated carbon nanotubes intercalated is subjected to ultrasonic reaction to obtain carbon nanotube modified aramid fiber slurry. S6. The carbon nanotube-modified aramid fiber slurry is subjected to high-pressure homogenization to obtain carbon nanotube-modified aramid nanofibers. Steps S1 and S2 are not in any particular order.
[0023] Specifically, in step S1, the mechanical treatment is a pulping process, with a pulping gap of 0.1mm to 0.5mm and a pulping speed of 20,000 rpm to 50,000 rpm.
[0024] Specifically, in step S1, a chemical pretreatment is performed in a mixed solution of N,N-dimethylacetamide (DMAC) and potassium hydroxide (KOH); wherein the mass concentration of potassium hydroxide in the mixed solution is 0.5%~2%. Specifically, in step S1, the chemical pretreatment reaction temperature is 60~80℃, and the reaction time is 2~4 hours. Excessive reaction time or temperature will cause the aramid fibers to dissolve, resulting in excessive damage to the aramid fibers.
[0025] Specifically, in step S1, the mass ratio of aramid fiber to the mixed solution is 1:(100~200).
[0026] Specifically, in step S1, the length of the aramid fiber after pulping is 50μm~100μm and the diameter is 10μm~30μm; the length of the aramid fiber after chemical pretreatment is 20~60μm and the diameter is 5~20μm.
[0027] It should be noted that the aramid fiber slurry after chemical pretreatment in step S1 is used directly in step S3 for mixing without washing or drying.
[0028] Specifically, in step S2, the carboxylation reaction is carried out at a temperature of 60-80°C for 4-10 hours.
[0029] Specifically, in step S2, the ratio of carbon nanotubes to mixed acid is (1~5) g: 100 mL.
[0030] Specifically, in step S2, the mixed acid is sulfuric acid and nitric acid; the volume ratio of sulfuric acid to nitric acid is (1~3):1.
[0031] In some embodiments, 98% concentrated sulfuric acid and 70% nitric acid are used.
[0032] It should be noted that the carboxylation reaction in step S2 is carried out under water bath heating conditions; after the reaction is complete, the solution is removed by vacuum filtration and repeatedly washed with deionized water until neutral to obtain carboxylated carbon nanotubes. During the vacuum filtration process, the filter membrane is a polytetrafluoroethylene membrane or a mixed cellulose ester membrane with a pore size of 1μm~10μm. Polytetrafluoroethylene membranes or mixed cellulose ester membranes have good corrosion resistance.
[0033] Specifically, in step S4, the low-pressure homogenization pressure is 20MPa~40MPa, and the homogenization time is 1~2h.
[0034] In some embodiments, in step S4, the homogenizing valve in the homogenizer must be made of one of diamond, ceramic or stainless steel, and the sealing ring must be a corrosion-resistant gasket made of one of polytetrafluoroethylene, Teflon or perfluoroether rubber.
[0035] Specifically, in step S5, the frequency of the ultrasonic reaction is 20kHz~30kHz, the reaction time is 1~2h, and the reaction temperature is 60℃~80℃.
[0036] It is understood that in step S5, the ultrasonic reaction causes the carboxyl groups on the carboxylated carbon nanotubes to chemically bond with the molecular chains of aramid fibers; after the reaction is completed, the product is centrifuged and washed with deionized water to remove unreacted carboxylated carbon nanotubes and residual chemical reagents, and purified carbon nanotube modified aramid fiber slurry is obtained.
[0037] Specifically, in step S6, the high-pressure homogenization pressure is 100MPa~120MPa, and the homogenization time is 0.5~1.5h.
[0038] More specifically, the high-pressure homogenization pressure in step S6 is 3 to 5 times the low-pressure homogenization pressure in step S4.
[0039] It is understandable that the high-pressure homogenization process in step S6 causes the aramid fibers to dissociate into nanofibers, while the carboxylated carbon nanotubes are firmly attached to the surface of the aramid nanofibers or embedded in them through chemical bonds, thus obtaining carbon nanotube-modified aramid nanofibers.
[0040] The present invention also provides a modified aramid nanofiber, which is prepared by the preparation method provided by the present invention.
[0041] In this invention, there are no special restrictions on the types of aramid fibers and carbon nanotubes. In some embodiments, the aramid fibers are para-aramid short-cut fibers with a fiber length of 3-7 mm and a fiber diameter of 5-12 μm; the carbon nanotubes are single-walled carbon nanotubes with an outer diameter of 1-2 nm and a purity of >90%; however, this is not a limitation of the technology of this invention.
[0042] To better illustrate the embodiments of the present invention, the present invention will be further described in detail below through specific examples.
[0043] Example 1
[0044] The specific steps for preparing a carbon nanotube-modified aramid nanofiber are as follows: S1. Take 10g of aramid fiber, add 100mL of deionized water, transfer to a disc mill, set the disc gap to 0.1mm, milling speed to 30000rpm, and mill for 20min to obtain aramid fiber slurry. Take 5g of KOH and 300g of DMAC, slowly add KOH to DMAC, and heat in a 60℃ water bath, stirring for 1h until KOH is completely dissolved to obtain a mixed solution. Add the aramid fiber slurry to the mixed solution and place it in a 80℃ water bath for chemical pretreatment, stirring for 2h to obtain pretreated aramid fiber slurry.
[0045] After pulping, the aramid fibers have a length of 70 μm and a diameter of 20 μm; after chemical pretreatment, the aramid fibers have a length of 40 μm and a diameter of 10 μm.
[0046] S2. Take 2g of carbon nanotubes and add 200mL of a mixed acid of sulfuric acid and nitric acid, where the volume ratio of sulfuric acid to nitric acid is 2:1. After ultrasonic dispersion at room temperature, place the mixture in an 80℃ constant temperature water bath and react for 4 hours. After the reaction is complete, cool to room temperature and vacuum filter using a 1μm PTFE filter membrane. Collect the filter cake and wash it repeatedly with deionized water until neutral. Place the washed product in an oven and dry to obtain carboxylated carbon nanotube powder.
[0047] S3. The obtained carboxylated carbon nanotube powder is mixed with the pretreated aramid fiber slurry and ultrasonically dispersed to obtain a mixed slurry.
[0048] S4. Transfer the mixed slurry to a high-pressure homogenizer for low-pressure homogenization. Set the homogenization pressure to 20 MPa and the homogenization time to 1.5 h to obtain aramid fiber slurry intercalated with carboxylated carbon nanotubes.
[0049] S5. The aramid fiber slurry with carboxylated carbon nanotubes intercalated to be transferred to a stainless steel reactor and placed in a constant temperature water bath at 65°C. The ultrasonic frequency was set to 25kHz, and the reaction time was 1.5h. After the ultrasonic reaction was completed, the slurry was centrifuged and washed at 8000rpm for 15min each time, for a total of 4 washes, until the supernatant was clear and transparent and the pH was neutral, thus obtaining the carbon nanotube modified aramid fiber slurry.
[0050] S6. Transfer the carbon nanotube-modified aramid fiber slurry to a high-pressure homogenizer for high-pressure homogenization. Set the homogenization pressure to 100 MPa and the homogenization time to 1 hour to obtain carbon nanotube-modified aramid nanofibers.
[0051] The carbon nanotube-modified aramid nanofibers prepared in this embodiment have an average diameter of 120 nm, an average length of 10.1 μm, and a carbon nanotube retention rate of 85.6%.
[0052] Example 2
[0053] This embodiment uses the same method as in Example 1 to prepare a carbon nanotube modified aramid nanofiber, the difference being: in step S1, the disc milling gap is set to 0.3 mm and the milling speed is 50000 rpm; 6 g of KOH and 300 g of DMAC are placed in a water bath at 70 °C for chemical pretreatment and stirred for 3 h.
[0054] Example 3
[0055] This embodiment uses the same method as in Example 1 to prepare a carbon nanotube modified aramid nanofiber, except that in step S2, the mixture is placed in a 70°C constant temperature water bath and reacted for 7 hours.
[0056] Example 4
[0057] This embodiment uses the same method as in Example 1 to prepare a carbon nanotube modified aramid nanofiber, the difference being that in step S4, the low-pressure homogenization treatment is set with a homogenization pressure of 40 MPa and a homogenization time of 1 h.
[0058] In step S6, the high-pressure homogenization process is set with a homogenization pressure of 120 MPa and a homogenization time of 0.5 h.
[0059] Example 5
[0060] This comparative example uses the same method as Example 1 to prepare a carbon nanotube modified aramid nanofiber, the difference being that: in step S6, the homogenization pressure of the high-pressure homogenization treatment is set to 120 MPa. At this time, the high-pressure homogenization pressure is 6 times that of the low-pressure homogenization pressure, which is not within the range of 3 to 5 times limited by this invention.
[0061] Comparative Example 1 This comparative example uses the same method as Example 1 to prepare a carbon nanotube modified aramid nanofiber, the difference being that: no chemical pretreatment was performed on the aramid fiber slurry after pulping.
[0062] The carbon nanotube-modified aramid nanofibers obtained in this comparative example have an average diameter of 810 nm, an average length of 15.1 μm, and a carbon nanotube retention rate of 11.2%.
[0063] Comparative Example 2 This comparative example uses the same method as Example 1 to prepare a carbon nanotube-modified aramid nanofiber, except that the carbon nanotubes are not carboxylated.
[0064] The carbon nanotube-modified aramid nanofibers obtained in this comparative example have an average diameter of 182 nm, an average length of 3.1 μm, and a carbon nanotube retention rate of 1.3%.
[0065] Comparative Example 3 This comparative example uses the same method as Example 1 to prepare a carbon nanotube modified aramid nanofiber, except that the mixed slurry of carbon nanotubes and aramid fibers is not subjected to low-pressure homogenization treatment.
[0066] The carbon nanotube-modified aramid nanofibers obtained in this comparative example have an average diameter of 132 nm, an average length of 12.8 μm, and a carbon nanotube retention rate of 23.9%.
[0067] Comparative Example 4 This comparative example uses the same method as Example 1 to prepare a carbon nanotube modified aramid nanofiber, the difference being that the carbon nanotubes and aramid fiber slurry after low-pressure homogenization were not subjected to ultrasonic chemical reaction.
[0068] The carbon nanotube-modified aramid nanofibers obtained in this comparative example have an average diameter of 125 nm, an average length of 12.3 μm, and a carbon nanotube retention rate of 21.6%.
[0069] Comparative Example 5 This comparative example uses the same method as Example 1 to prepare a carbon nanotube modified aramid nanofiber, except that high-pressure homogenization was not performed.
[0070] The carbon nanotube-modified aramid nanofibers obtained in this comparative example have an average diameter of 125 nm, an average length of 12.3 μm, and a carbon nanotube retention rate of 21.6%.
[0071] Comparative Example 6 This comparative example uses the same method as Example 1 to prepare a carbon nanotube modified aramid nanofiber, the difference being that: in step S4, a high-pressure homogenization treatment is performed, with the homogenization pressure set to 100 MPa and the homogenization time to 1 h.
[0072] Step S6 involves low-pressure homogenization, with a homogenization pressure of 20 MPa and a homogenization time of 1.5 h.
[0073] Comparative Example 7 This comparative example uses the same method as Example 1 to prepare a carbon nanotube modified aramid nanofiber, except that in step S1, 10g of KOH is taken.
[0074] The carbon nanotube-modified aramid nanofibers prepared in this comparative example have an average diameter of 80 nm, an average length of 10.0 μm, and a carbon nanotube retention rate of 83.2%.
[0075] Comparative Example 8 This comparative example uses the same method as Example 1 to prepare a carbon nanotube modified aramid nanofiber, except that in step S4, the homogenization pressure of the low-pressure homogenization treatment is set to 50 MPa.
[0076] The carbon nanotube-modified aramid nanofibers prepared in this comparative example have an average diameter of 105 nm, an average length of 12.2 μm, and a carbon nanotube retention rate of 61.2%.
[0077] Comparative Example 9 This comparative example uses the same method as Example 1 to prepare a carbon nanotube modified aramid nanofiber, except that in step S5, the ultrasonic reaction time is 0.5 h.
[0078] The carbon nanotube-modified aramid nanofibers prepared in this comparative example have an average diameter of 101 nm, an average length of 11.2 μm, and a carbon nanotube retention rate of 48.3%.
[0079] Comparative Example 10 This comparative example uses the same method as Example 1 to prepare a carbon nanotube modified aramid nanofiber, except that in step S6, the homogenization pressure of the high-pressure homogenization treatment is set to 80 MPa.
[0080] The carbon nanotube-modified aramid nanofibers prepared in this comparative example have an average diameter of 240 nm, an average length of 12.6 μm, and a carbon nanotube retention rate of 78.2%.
[0081] The performance of the carbon nanotube-modified aramid nanofibers prepared in the embodiments and comparative examples of this invention was tested, and the testing methods involved were as follows: (1) Fiber size characterization: scanning electron microscopy.
[0082] (2) Carbon nanotube retention rate: Refer to GB / T 37631-2019 "Test method for thermal decomposition temperature of chemical fibers", test conditions: air atmosphere, heating rate: 10-20℃ / min, temperature range 25℃-800℃, the final product is mainly carbon nanotubes, and the carbon nanotube retention rate is calculated accordingly.
[0083] (3) Tensile strength: Aramid nanofibers modified with carbon nanotubes were vacuum filtered to obtain nanofiber membranes. The tensile strength was measured in accordance with GB / T 12914-2018.
[0084] (4) Electrical conductivity: The electrical conductivity of the carbon nanotube-modified aramid nanofiber membrane was determined by the four-point probe method.
[0085] The performance test data of carbon nanotube-modified aramid nanofibers obtained in the examples and comparative examples are shown in Table 1.
[0086] Table 1 Performance test data of carbon nanotube-modified aramid nanofibers obtained in the examples and comparative examples
[0087] As can be seen from the data in Table 1, the carbon nanotube-modified aramid nanofibers obtained by the preparation method provided by this invention form a strong chemical bond and physical anchoring structure between the carbon nanotubes and the aramid matrix, effectively inhibiting the aggregation and shedding of carbon nanotubes. In terms of conductivity, the carbon nanotubes construct a complete conductive pathway in the aramid nanofiber network, and the conductivity is significantly improved compared with the unmodified sample. At the same time, the dispersion uniformity and long-term stability of carbon nanotubes in the matrix are significantly improved, showing significant advantages in terms of carbon nanotube anchoring strength, mechanical properties, conductivity, and dispersion stability.
[0088] The experimental comparison between Comparative Example 1 and Example 1 shows that the electrical conductivity decreases when the aramid fiber slurry after pulping is not chemically pretreated. This is because the aramid fiber structure without chemical pretreatment is dense and has few active sites, making it difficult for carbon nanotubes to effectively intercalate and chemically bond. Most carbon nanotubes are only physically adsorbed onto the fiber surface and are easily detached during post-processing. At the same time, insufficient fiber swelling also leads to poor subsequent high-pressure homogenization and dissociation, resulting in an increase in fiber diameter.
[0089] The experimental comparison between Comparative Example 2 and Example 1 shows that the electrical conductivity of the material decreases without carboxylation modification of the carbon nanotubes. This is because the surface of unmodified carbon nanotubes lacks active functional groups and cannot form covalent bonds with the aramid fiber molecular chains. They can only adhere to the fiber surface through weak interactions such as π-π stacking and hydrogen bonding, making them extremely prone to detachment during ultrasonic treatment and homogenization, resulting in severely insufficient interfacial bonding strength.
[0090] The experimental comparison between Comparative Example 3 and Example 1 shows that the electrical conductivity of the material decreases when the carbon nanotube and aramid fiber mixture is not subjected to low-pressure homogenization treatment. This is because without low-pressure homogenization treatment, carbon nanotubes cannot effectively insert into the interlayer gaps of the fiber at the macroscopic stage. The contact between carbon nanotubes and fibers is limited to surface collisions. Even if chemical bonding is subsequently formed through ultrasonic reaction, it can only occur on the fiber surface, and the internal embedding and deep anchoring of carbon nanotubes cannot be achieved.
[0091] The experimental comparison between Comparative Example 4 and Example 1 shows that the material properties deteriorate when the carbon nanotubes and aramid fiber slurry are not subjected to ultrasonic chemical reaction after low-pressure homogenization. This is because without ultrasonic chemical reaction, the carboxyl groups on the carbon nanotubes cannot form covalent bonds with the aramid molecular chains. The carbon nanotubes only exist inside the fiber through physical intercalation. Under the high shear force of subsequent high-pressure homogenization, most of the carbon nanotubes will be washed away and cannot achieve firm anchoring.
[0092] The experimental comparison between Comparative Example 5 and Example 1 shows that without high-pressure homogenization, the resulting product is a bundle of carbon nanotube-modified micron-sized aramid fibers, not nanofibers. The product cannot be stably dispersed in water and settles rapidly after standing, leading to a decline in material properties. This is because, without high-pressure homogenization, the chemically bonded carbon nanotubes in the aramid fibers retain their macroscopic morphology and cannot dissociate into nanofibers. Macroscopic fibers have a small specific surface area and limited active sites, failing to fully utilize the reinforcing and conductive functions of carbon nanotubes. Furthermore, the product cannot be used in applications requiring nanoscale structures.
[0093] The experimental comparison between Comparative Example 6 and Example 1 shows that the material performance deteriorates when the low-pressure homogenization and high-pressure homogenization conditions are interchanged. This is because when high-pressure homogenization is used first, the aramid fibers are dissociated into nanofibers before the carbon nanotubes are inserted. Subsequent low-pressure homogenization cannot allow the carbon nanotubes to enter the dissociated nanofibers. The carbon nanotubes and nanofibers can only form surface physical adsorption, and the deep intercalation structure of "intercalation first, then dissociation" cannot be achieved.
[0094] The experimental comparison between Comparative Example 7 and Example 1 shows that when KOH concentration is too high, obvious corrosion pits appear on the fiber surface, some fibers are over-dissolved, and the fiber length and diameter become smaller. This is because when the KOH concentration is too high, the chemical pretreatment has an excessively strong dissolving effect on the aramid fibers, leading to excessive damage to the fiber structure and breakage of molecular chains. Even with subsequent intercalation and bonding, it is difficult to restore the mechanical properties of the fibers, resulting in an "overtreatment" phenomenon.
[0095] The experimental comparison between Comparative Example 8 and Example 1 shows that a higher low-pressure homogenization pressure leads to a decrease in performance. This is because when the low-pressure homogenization pressure is too high, the mechanical shear force exceeds the fiber's tolerance limit, causing the fiber to dissociate prematurely before the carbon nanotubes are fully intercalated. The already intercalated carbon nanotubes also partially detach due to excessive shearing. At the same time, the prematurely dissociated fiber fragments cannot maintain effective contact with the carbon nanotubes in the subsequent ultrasonic reaction, ultimately resulting in a significant decrease in the anchoring effect.
[0096] The experimental comparison between Comparative Example 9 and Example 1 shows that a shorter ultrasonic reaction time results in a lower retention rate of carbon nanotubes and a decline in performance. This is because insufficient ultrasonic reaction time leads to incomplete chemical bonding between carboxylated carbon nanotubes and aramid fiber molecular chains. Only some carbon nanotubes form covalent bonds, while a large number remain in a state of physical adsorption or intercalation. These carbon nanotubes are prone to detachment during subsequent high-pressure homogenization, significantly reducing the bonding strength.
[0097] The experimental comparison between Comparative Example 10 and Example 1 shows that the high-pressure homogenization pressure is too low, resulting in insufficient nanofiber processing of aramid fibers. This leads to an increase in the average diameter and average length of the nanofibers, while simultaneously reducing their performance. This is because when the high-pressure homogenization pressure is below 100 MPa, the shear force and cavitation effect are insufficient to fully dissociate the aramid fibers bonded with carbon nanotubes into nanofibers. The product contains a large number of undissociated micron-sized fiber bundles and aggregates, and the conductive network formed by the carbon nanotubes is discontinuous. Consequently, the mechanical and electrical properties cannot reach the levels expected of nanoscale materials.
[0098] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are exhaustively listed. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0099] For those skilled in the art, various modifications and improvements can be made without departing from the concept of the present invention, and these modifications and improvements are all within the scope of protection of the present invention. The scope of protection of the present invention is defined by the appended claims.
Claims
1. A method for preparing modified aramid nanofibers, characterized in that, The preparation method includes the following steps: S1. The aramid fiber is first mechanically pulped and then chemically pretreated to obtain pretreated aramid fiber pulp. S2. Carbon nanotubes are ultrasonically dispersed evenly in a mixed acid solution and then subjected to a carboxylation reaction to obtain carboxylated carbon nanotubes. S3. Mix the obtained carboxylated carbon nanotubes with the pretreated aramid fiber slurry evenly to obtain a mixed slurry; S4. The mixed slurry is subjected to low-pressure homogenization to obtain aramid fiber slurry with carboxylated carbon nanotubes intercalated. S5. The aramid fiber slurry with carboxylated carbon nanotubes intercalated is subjected to ultrasonic reaction to obtain carbon nanotube modified aramid fiber slurry. S6. The carbon nanotube-modified aramid fiber slurry is subjected to high-pressure homogenization to obtain carbon nanotube-modified aramid nanofibers. Steps S1 and S2 are not in any particular order.
2. The method for preparing modified aramid nanofibers according to claim 1, characterized in that, In step S1, the mechanical treatment is a pulping process, with a pulping gap of 0.1mm to 0.5mm and a pulping speed of 20,000 rpm to 50,000 rpm.
3. The method for preparing modified aramid nanofibers according to claim 1, characterized in that, In step S1, chemical pretreatment is carried out in a mixed solution of N,N-dimethylacetamide and potassium hydroxide; In the mixed solution, the mass concentration of potassium hydroxide is 0.5% to 2%. The mass ratio of aramid fiber to the mixed solution is 1:(100~200).
4. The method for preparing modified aramid nanofibers according to claim 1, characterized in that, In step S1, the length of the aramid fiber after pulping is 50μm~100μm and the diameter is 10μm~30μm; The chemically pretreated aramid fibers have a length of 20μm~60μm and a diameter of 5μm~20μm.
5. The method for preparing modified aramid nanofibers according to claim 1, characterized in that, In step S1, the reaction temperature for chemical pretreatment is 60~80℃, and the reaction time is 2~4h; In step S2, the carboxylation reaction is carried out at a temperature of 60-80°C for 4-10 hours.
6. The method for preparing modified aramid nanofibers according to claim 1, characterized in that, In step S2, the mixed acid is sulfuric acid and nitric acid; The volume ratio of sulfuric acid to nitric acid is (1~3):
1.
7. The method for preparing modified aramid nanofibers according to claim 1, characterized in that, In step S4, the low-pressure homogenization pressure is 20MPa~40MPa, and the homogenization time is 1~2h; In step S6, the high-pressure homogenization pressure is 100MPa~120MPa, and the homogenization time is 0.5~1.5h.
8. The method for preparing modified aramid nanofibers according to claim 7, characterized in that, The high-pressure homogenization pressure is 3 to 5 times that of the low-pressure homogenization pressure.
9. The method for preparing modified aramid nanofibers according to claim 1, characterized in that, In step S5, the frequency of the ultrasonic reaction is 20kHz~30kHz, the reaction time is 1~2h, and the reaction temperature is 60℃~80℃.
10. A modified aramid nanofiber, characterized in that, Prepared by the method according to any one of claims 1-9.
Citation Information
Patent Citations
Method for modifying aramid fiber by using carbon nano tubes
CN101831800A